Transforming Teaching to learning with ICT - Syaiful Rohim (Universitas Sarjanawiyata Tamansiswa, 2017)
The changes paradigm from â€œteachingâ€ to â€œlearning doesnâ€™t always related with something that happen in the class such as interaction teacher and students, but also involves the changes of paradigm and it must be done by the institution as a system in an organization and it must be done by all persons. The changes mindset from teaching to learning, which gives some lesson to the planning must be done by the lecture or teacher, more over the development of information and communication technology in this era globalization is already developed. So it needs to be done the changes of learning system by using models or methods which can push the students to be an active learner. The using of ICT maybe can be the solution of this problem. Thatâ€™s why lecture or teacher must follow the development of Information and Communication Technology (ICT) in learning process and also can apply in the environment which has been planed.